การบริหารจัดการเคเบิลทีวีท้องถิ่นจังหวัดอุบลราชธานี - สิริรัมภา การะนนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The local cable televisions in Ubonratchathani province have 2 distinct structures. The founder of Ubonratchathani Sophon Cable TV was the ex-politician in eastern Thailand, the company executives were the group of businessman in eastern region join with local trades. While Ratchathani Cable TV was originated and operates by the group of local businessman. Those structures affected the local channel management: administration, policy, programming, and marketing, which caused their local program s genre and content to be different. The result found that Sophon Channel s program genre was mostly news, talk and interview, its content was mainly about local government sectors information, and the entertainment in arts and culture. While RTV Channel s program genre was mostly news and music. Its main content was information about local society and culture, medicine and public health, and its entertainment program presented local arts and culture matter mainly. While the advertising program content of both channels were mostly local commerce and services. By comparing the local program s content of the 2 companies, we found that the company which was originated and operate by local businessman mainly presented local-involved stories. But the other, settled up by non-local man, mostly presented general information that was not local subject specifically. So the ownership might be the important factor which had an effect on the production and presentation of genre and content of local programs